Analisis Customer Loyalty dan Customer Satisfaction dalam Penggunaan Aplikasi Dana melalui Digital Customer Experience - Wiranto, Heri; Teduh Dirgahayu, Raden; Andri Setiawan, Mukhammad (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
A good digital experience enhances customer loyalty and satisfaction, encouraging repeat usage and recommendations. However, the impact of customer experience on loyalty and satisfaction is often overlooked. This study aims to examine the effects of digital experience on customer loyalty and satisfaction in the DANA digital wallet. The study employs a quantitative method with Rank Spearman analysis, where Customer Experience serves as the independent variable, and Customer Loyalty and Customer Satisfaction are the dependent variables. Data was collected through a Google Form questionnaire using a Likert scale, with 100 respondents meeting the criteria of having used the DANA application for at least five months and having completed at least ten transactions with a minimum top-up of IDR 100,000. Our findings indicate that the digital customer experience on DANA has a significantly positive impact on both customer loyalty and customer satisfaction, which are closely related. Customer satisfaction substantially influences customer loyalty, confirming the strong relationship between the two. This suggests that a positive digital experience on the DANA platform not only increases satisfaction but also strengthens customer loyalty, which is crucial for long-term business success.